Long-term Exposure to Particulate Matter Constituents and the Incidence of Coronary Events in 11 European Cohorts. Issue 4 (July 2015) - Wolf, Kathrin; Stafoggia, Massimo; Cesaroni, Giulia; Andersen, Zorana Jovanovic; Beelen, Rob; Galassi, Claudia; Hennig, Frauke; Migliore, Enrica; Penell, Johanna; Ricceri, Fulvio; Sørensen, Mette; Turunen, Anu W.; et al.
Abstract : Background: Long-term exposure to particulate matter (PM) has been associated with increased cardiovascular morbidity and mortality but little is known about the role of the chemical composition of PM. This study examined the association of residential long-term exposure to PM components with incident coronary events. Methods: Eleven cohorts from Finland, Sweden, Denmark, Germany, and Italy participated in this analysis. 5, 157 incident coronary events were identified within 100, 166 persons followed on average for 11.5 years. Long-term residential concentrations of PM < 10 μm (PM10 ), PM < 2.5 μm (PM2.5 ), and a priori selected constituents (copper, iron, nickel, potassium, silicon, sulfur, vanadium, and zinc) were estimated with land-use regression models. We used Cox proportional hazard models adjusted for a common set of confounders to estimate cohort-specific component effects with and without including PM mass, and random effects meta-analyses to pool cohort-specific results. Results: A 100 ng/m³ increase in PM10 K and a 50 ng/m³ increase in PM2.5 K were associated with a 6% (hazard ratio and 95% confidence interval: 1.06 [1.01, 1.12]) and 18% (1.18 [1.06, 1.32]) increase in coronary events. Estimates for PM10 Si and PM2.5 Fe were also elevated. All other PM constituents indicated a positive association with coronary events. When additionally adjusting for PM mass, the estimates decreased except for K. Conclusions: This multicenter study of 11 European cohorts pointed to an association between long-term exposure to PM constituents and coronary events, especially for indicators of road dust. Abstract : Supplemental Digital Content is available in the text.